Dorsal root ganglion toll-like receptor 4 signaling contributes to oxaliplatin-induced peripheral neuropathy. Issue 5 (2nd May 2022) - Illias, Amina M.; Yu, Kai-Jie; Hwang, Seon-Hee; Solis, Jacob; Zhang, Hongmei; Velasquez, Jose F.; Cata, Juan P.; Dougherty, Patrick M.
Abstract : Oxaliplatin treatment in male and female rats produces mechanical hyperalgesia and increased signaling of toll-like receptor 4 (TLR4) in the dorsal root ganglion. Intrathecal cotreatment with the TLR4 antagonist lipopolysaccharide derived from Rhodobacter sphaeroides with oxaliplatin prevents both the behavioral phenotype and the increase in dorsal root ganglion TLR4 signaling. Abstract: Activation of toll-like receptor 4 (TLR4) in the dorsal root ganglion (DRG) and spinal cord contributes to the generation of paclitaxel-related chemotherapy-induced peripheral neuropathy (CIPN). Generalizability of TLR4 signaling in oxaliplatin-induced CIPN was tested here. Mechanical hypersensitivity developed in male SD rats by day 1 after oxaliplatin treatment, reached maximum intensity by day 14, and persisted through day 35. Western blot revealed an increase in TLR4 expression in the DRG of oxaliplatin at days 1 and 7 after oxaliplatin treatment. Cotreatment of rats with the TLR4 antagonist lipopolysaccharide derived from Rhodobacter sphaeroides ultrapure or with the nonspecific immunosuppressive minocycline with oxaliplatin resulted in significantly attenuated hyperalgesia on day 7 and 14 compared with rats that received oxaliplatin plus saline vehicle. Immunostaining of DRGs revealed an increase in the number of neurons expressing TLR4, its canonical downstream signal molecules myeloid differentiation primary response gene 88 (MyD88) and TIR-domain–containing adapter-inducing interferon-β, at both day 7 and day 14 after oxaliplatin treatment. These increases were blocked by cotreatment with either lipopolysaccharide derived from Rhodobacter sphaeroides or minocycline. Double staining showed the localization of TLR4, MyD88, and TIR-domain–containing adapter-inducing interferon-β in subsets of DRG neurons. Finally, there was no significant difference in oxaliplatin-induced mechanical hypersensitivity between male and female rats when observed for 2 weeks. Furthermore, upregulation of TLR4 was detected in both sexes when tested 14 days after treatment with oxaliplatin. These findings suggest that the activation of TLR4 signaling in DRG neurons is a common mechanism in CIPN induced by multiple cancer chemotherapy agents.